Supply Chain Risks and Uncertainties in the Kenya Petroleum Industry - Ndungu, Linda Njeri (2016)
Purpose- The purpose of this research is to identify the supply chain risks and uncertainties plaguing the Kenya petroleum industry and provide recommendations on mitigation strategies that can be applied to reduce their impact.